Bantu education: the black teacher's lived experience of conflict - Ramabulana, Ronald Thifulufhelwi (Rhodes University, Faculty of Humanities, Department of Psychology, 1991)
This work is a descriptive phenomenological study of the experience of conflict that is lived by black teachers in the Bantu Education context. Subjects are teachers from the East Rand and Eastern Cape who have high school teaching experience that ranges from 1 to 15 years. The conflict researched was defined as those situations in which the teacher faced demands or expectations from different interest groups which were incompatible or negated each other. The Subjects of this research were six teachers who were interviewed for case material. The phenomenological case study design was used. Data collection consisted of in-depth interviews while analysis followed the phenomenological method developed at Duquesne University. This was an exploratory study which identified two major forms of conflict. The first exists between the teacher's expectation of teaching and the education authorities' expectation of how and what the teacher should teach in lessons. The second form of conflict identified is that in which the teacher's allegiance to one social group or ideology is violated by the teacher's participation in a system of education that negates his/her view about the South African sociopolitical situation. In the latter case the teacher is forced to comply with commitments or demands placed on him/her which negate each other. Van den Berg's theory of plural existence was used to inform data analysis and so was the theory of cognitive change and inconsistency.
Keywords: Conflict (Psychology); Teachers, Black -- Psychology Case studies; Teachers, Black -- South Africa; Education -- South Africa